Anaerobic oxidation of methane coupled to denitrification: fundamentals, challenges, and potential. Issue 19 (2nd November 2018) - Lee, Hyung-Sool; Tang, Youneng; Rittmann, Bruce E.; Zhao, He-Ping
Abstract: Anaerobic treatment of dilute wastewater (e.g., municipal sewage) is promising due to energy recovery and lessened operating costs, both of which can significantly improve the sustainability of wastewater management over traditional activated sludge treatment. Discharge of dissolved methane and the lack of nitrogen removal are challenges for widespread adoption of anaerobic wastewater treatment. Anaerobic oxidation of methane coupled to denitrification (AOM-D) can overcome both challenges in a complementary way, thus preserving the benefits of anaerobic treatment of dilute wastewater. This review first presents the principles of AOM-D, focusing on pathways and thermodynamics. Second, energy and economic benefits are assessed for anaerobic treatment of dilute wastewater. Third, the review addresses the technical challenges inherent to implementing AOM-D in suspended-growth systems and outlines the advantages of membrane biofilm reactors (MBfRs) for AOM-D applications. Finally, the review develops a model of AOM-D in an MBfR and uses the model to show the conditions that achieve fast denitrification kinetics simultaneously with a very low concentration of dissolved methane.